تطبيق مبادئ الحوكمة المؤسسية وإسهامها في تنمية الموارد البشرية : دراسة ميدانية على قطاع التأهيل بوزارة التربية والتعليم في سلطنة عمان - قصابية، سلوى سيف علي
The study aimed to identify the reality of the level of application of governance principles in rehabilitation sector at the Ministry of Education from the perspectives of employees in human development sector in the ministry and beneficiaries from rehabilitation programs, determine the contribution of governance principles application in promoting human resources development for employees in the Ministry of Education and beneficiaries from rehabilitation programs. The study population included (2048) beneficiaries from human development programs (in rehabilitation sector) at the Ministry of Education and (113) employees in the Human Resources Development Sector in the educational governorates and the Ministry’s General Office. The study sample included (408) beneficiaries and employees, as there were (322) beneficiaries of rehabilitation programs provided by the Ministry of Education in the Sultanate of Oman, and (86) employees in supervisory positions in the General Directorate for Human Resources Development. The researcher used the descriptive analytical method, and developed a questionnaire of (65) distributed in (6) domains, due to some theoretical literature. The findings revealed that: The general level of application of governance principles in rehabilitation sector at the Ministry of Education: came with moderate degree from the perspectives of employees in human development sector at the ministry, as well as those targeted by rehabilitation programs. The weak contribution of variables (partnership, transparency, accountability) in promoting human resources development from the perspectives of employees in human resources development, and justice is the only principle of governance that contributes to enhancing human resources development from the perspectives of employees in human resource development. The contribution of variables (partnership, transparency, accountability) in enhancing the development of human resources from the perspectives of beneficiaries in the rehabilitation programs. This confirms that the application of the three principles of governance (partnership, justice, accountability) contributes to enhancing the development of human resources from the perspectives of beneficiaries in rehabilitation programs. The study recommended the need to adopt international standards for measuring the quality of governance in the rehabilitation sector at the Ministry of Education, and attract expertise in administrative fields to develop vision for the mechanism of spreading the culture of governance in the rehabilitation sector.